Perjalanan Kejayaan Kerajaan Safawi Masa Abbas I dan Regresi Kerajaan Safawi Di Persia Sepeninggal Abbas I - Dzikra, Aulia Mar'atu; Febrina, Dina; Roza, Ellya (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
After Shah Abbas I died in 1629, the Safawi Kingdom began to decline. Abbas I brought Safawi to the pinnacle of glory with political stability, a strong military, and a thriving economy. However, his successor, Shah Safi I, was unable to maintain the achievement. His government was weakened by reliance on incompetent advisers and widespread corruption. In addition, external threats such as the Ottoman and Uzbek Empire attacks further exacerbated the situation. They took advantage of the Safavid weakness to expand their territory and undermine the stability of the kingdom. The previously prosperous economy also began to collapse due to the inability of the rulers to manage trade. Various rebellions and internal conflicts have further undermined the Safavid power. The rulers after Abbas I were unable to restore political and economic power, which ultimately led the kingdom to collapse in the mid-18th century. This paper examines the factors that led to the decline of the Safavid post-Abbas I.